(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
The continuous development of human needs leads to increased demand for electrical energy, which is increases the complexity of power systems. During abnormal operating conditions, such as a high inductive loads, nonlinear loads, or may be some faults that leads to the deterioration of the power quality of the power system (swells or voltage drops). Reactive power compensation is linked to voltage regulation; traditional methods that use constant capacitor banks lack the flexibility and dynamic potential to satisfy power quality standards. In this paper proposed StatCom one of the more recent FACTS devices is used to quickly and accurately manage reactive power, which enhances the efficiency of electrical power transmission and distribution networks. This paper discusses the use of STATCOM for two types of loads: inductive loads and nonlinear loads. The effectiveness of STATCOM systems in compensating for reactive power losses and mitigating the effects of harmful harmonics caused by nonlinear loads was demonstrated. MATLAB Simulink was used to achieve the results.